2020
DOI: 10.1002/hyp.13771
|View full text |Cite
|
Sign up to set email alerts
|

Estimating bed material fluxes upstream and downstream of a controlled large bifurcation ‐ the Mississippi‐Atchafalaya River diversion

Abstract: Bed material transport at river bifurcations is crucial for channel stability and downstream geomorphic dynamics. However, measurements of bed material transport at bifurcations of large alluvial rivers are difficult to make, and standard estimates based on the assumption of proportional partitioning of flow and bedload transport at bifurcations may be erroneous. In this study, we employed a combined approach based on observed topographic change (erosion/deposition) and bed material transport predicted from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…If Hu et al (2016) had focused on the whole Jingjiang reach, we believe that the two |ψ| values would have been more comparable. Similar erosion-deposition promotion events caused by water-sediment diversion and afflux along the mainstream have also been observed in other rivers, such as the Yellow River (Pan et al, 2015), Mississippi River (Kemp et al, 2014;Wang and Xu, 2020), and Amazon River (Li et al, 2020).…”
Section: Erosion-deposition Promotion In Different Mainstream Reachessupporting
confidence: 70%
“…If Hu et al (2016) had focused on the whole Jingjiang reach, we believe that the two |ψ| values would have been more comparable. Similar erosion-deposition promotion events caused by water-sediment diversion and afflux along the mainstream have also been observed in other rivers, such as the Yellow River (Pan et al, 2015), Mississippi River (Kemp et al, 2014;Wang and Xu, 2020), and Amazon River (Li et al, 2020).…”
Section: Erosion-deposition Promotion In Different Mainstream Reachessupporting
confidence: 70%
“…The much gentler slope (i.e., −0.7 × 10 −4 , 0.2 × 10 −3 , and 0.4 × 10 −3 ) of the water surface in the Atchafalaya River natural channel under high, medium, and low flow conditions has played a critical role in sediment siltation and channel aggradation. Wang and Xu (2020) reported that in the mainstem Mississippi, the percentage of bed material diversion (83%) is larger than the percentage of flow diversion (76%). Consequently, riverbed aggradation progressed in the mainstem Mississippi River downstream of the diversion structures with the disproportional flow–sediment ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that Yang's (1973) formula was most robust because its accuracies were least sensitive to the fluctuation of water depth, dimensionless shear velocity, dimensionless unit stream power, Froude number, and sediment concentration. In a recent study, Wang and Xu (2020) estimated daily BMLs at the Mississippi–Atchafalaya River diversion during 2004–2013 using Yang's Equation (Yang, 1973).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys were conducted by the USACE at multiple reaches in these locations to monitor diversion changes between 1880 and 1951. More recent studies have shown these patterns to persist in these reaches even after the construction of the ORCS (Knox and Latrubesse, 2016; Wang and Xu, 2018, 2020; Xu et al ., 2021).…”
Section: Introductionmentioning
confidence: 98%